Sustainability education in India: A discourse in education development - Joseph, Shaji; Patil, Kanchan; Kulkani, Apoorva; John, Michele (Taylor and Francis, 2025)
Since the 1970s various initiatives have been introduced to bring sustainability education into the Indian curricula. However, most of these initiatives have been focused on environmental sustainability. In primary and secondary education sustainability has been incorporated into a variety of subjects. The higher education sector in India has traditionally focused on education for employment and has only recently started to include a sustainability focus. Universities initiated education for sustainability only after the introduction of the SDGs in 2015. This chapter explores the sustainability initiatives of both early school education and higher education in India. It also explores the critical interrelationship between sustainability education and values education. The data used are collected mostly from secondary data, use cases, government, NGO and university websites and research papers. The chapter has also documented some best practice that can be used as vantage points to implement education for sustainable development in India.